PENINGKATAN KEMAMPUAN MENULIS NASKAH DRAMA DENGAN PENDEKATAN CONTEXTUAL TEACHING LEARNING (CTL) - Ahmad Syaeful Rahman (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2017)
The study is title “The Increased to Write Drama Manuscript With Contextual teaching Learning (CTL) Approach” which alms to develop students ability to write drama manuscript for MTs. eight grade with approach of contextual teaching learning (CTL). This research was carried out on eight grade student one of MTs. Mathla’ul Anwar 2 Bogor, as many as 47 students. The method research used is action research method. The instrument used in this study include: 1) observation sheet, 2) interview guide, 3) free essays for test writing drama manuscript, 4) documentation. The result showed that there increased ability to write drama manuscript with approach of contextual teaching learning (CTL) in eight grade student MTs. it is characterized by an increase in the average value of the test’s ability to write a drama manuscript. The increase in the average value of the pretest to cycle 1 was 15% and from cycle 1 to cycle 2 increased 4%. The mayor influence of the contextual teaching learning application the use of video impressions drama performances and discussion of video impressions drama performances and the use of media drama.